Anti-ultraviolet tooling fabric and preparation method thereof
By acid amyotrophizing the nylon matrix and compounding it with lignin fiber nanofiber and graphyne, nanosilicon dioxide is used as a reinforcing material to solve the lack of breathability and softness of existing UV-proof tooling fabrics, and improve the The ultraviolet barrier properties and wear resistance of the fabric are achieved, achieving higher protection and environmental protection performance.
Patent Information
- Application Number
- CN202411181787.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-27
- Publication Date
- 2025-01-10
AI Technical Summary
The existing UV-proof tooling fabrics are difficult to meet the needs of modern workers in terms of breathability and softness, and traditional technologies have limitations in protective performance and durability, which cannot effectively protect workers from ultraviolet radiation and accelerate tooling aging.
By acid-aminolation modification of the nylon matrix and composited with lignin fiber nanofibers and graphyne, nanosilicon dioxide is used as a reinforcing material to enhance the UV barrier properties, wear resistance and biodegradability of the fabric.
It significantly improves the UV barrier properties, wear resistance and biodegradability of the fabric, enhances wear comfort and durability, and meets the high performance and environmental protection requirements of modern tooling fabrics.
Smart Images

Figure CN119287549A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of textile production and processing, and in particular relates to an anti-ultraviolet workwear fabric and a preparation method thereof. Background Art
[0002] Research on anti-UV workwear fabrics began in the late 20th century. The earliest anti-UV fabrics mainly achieved UV blocking through physical shielding and chemical absorption. Physical shielding mainly depends on the weaving density and thickness of the fabric, while chemical absorption depends on the addition of UV absorbers. However, these traditional technologies have certain limitations in performance and comfort, especially in terms of breathability and softness, which are difficult to meet the needs of modern workers. The problem of ultraviolet radiation in modern industrial working environments has received increasing attention, especially for workers working outdoors or exposed to strong light environments. Long-term ultraviolet exposure may not only cause skin damage, but also accelerate the aging of workwear and affect its protective performance. Therefore, society's demand for anti-UV workwear fabrics is increasing, especially for its comfort, durability and protective effect.
[0003] As a new type of environmentally friendly material, lignin fiber nanofiber has attracted widespread attention. Lignin is an important component of plant cell walls and has excellent biodegradability and regeneration ability. Lignin itself has a certain ability to adsorb and shield ultraviolet rays. After nano-processing, its surface active sites increase, which can effectively improve the UV blocking performance of fabrics. Lignin comes from natural plants and has excellent biodegradability, which can effectively reduce the environmental burden during the production and use of fabrics. Lignin fiber nanofibers can improve the softness and breathability of fabrics, thereby improving wearing comfort.
[0004] As a new type of carbon material, Graphdyne has excellent light absorption and heat dissipation properties, and can effectively absorb ultraviolet rays, thereby reducing direct exposure of ultraviolet rays to the skin. The stability and high temperature resistance of Graphdyne can enhance the durability of fabrics and extend their service life.
[0005] Nano-silica can effectively block the penetration of ultraviolet rays and provide an additional layer of protection through its high surface area. At the same time, it can improve the strength and tear resistance of the fabric, making it more durable in harsh working environments. Summary of the invention
[0006] The purpose of the present invention is to provide an anti-ultraviolet workwear fabric and a preparation method thereof, in particular, by acid amination-modifying a nylon matrix with lignin fiber nanofibers and compounding it with graphyne and nano-silica, the comprehensive performance of the anti-ultraviolet workwear fabric is significantly improved.
[0007] The specific technical solutions are as follows: A UV-proof workwear fabric and a preparation method thereof. The raw materials used to manufacture the UV-proof workwear fabric are composed of: 80-100 parts of nylon matrix, 5-10 parts of lignin cellulose nanofibers, 5-10 parts of ammonia, 80-100 parts of acid treatment agent, 40-60 parts of ammonia water, 180-200 parts of dimethylsulfamide, 0.5-1 part of p-toluenesulfonic acid, 500-700 parts of deionized water, 0.1-0.5 parts of hydroxytoluene, 2-5 parts of nano-silicon dioxide, and 0.5-2 parts of graphene. The preparation method of the UV-proof workwear fabric comprises the following steps: S1 Pretreatment of wood cellulose nanofibers: Add 5-10 parts of lignin cellulose nanofibers and 80-100 parts of acid treatment agent into a multifunctional reactor, stir at a rate of 1300-1500 r / min, and mix and stir at 10-30°C for 180-240 minutes; S2 dispersion of wood cellulose nanofibers: continue to add 200-300 parts of deionized water to the multifunctional reactor in step S1, with a stirring rate of 1000-1200 r / min, mix and stir at 10-30°C for 20-30 minutes, and ultrasonically treat for 30-60 minutes to obtain a uniform wood cellulose nanofiber suspension; S3 dissolving nylon: add 80-100 parts of nylon matrix and 180-200 parts of dimethylsulfamide to the multifunctional reactor in sequence, and stir at a rate of 1000-1200 r / min for 120-240 minutes to completely dissolve the nylon matrix; S4 amino modification: a. Add the lignocellulose nanofiber suspension in step S2 and the dissolved nylon in step S3 into a multifunctional reactor, and stir at a rate of 1000 to 1200 r / min for 120 to 240 minutes; b. Add 40-60 parts of ammonia water, 0.5-1 parts of p-toluenesulfonic acid, and 0.1-0.5 parts of hydroxytoluene to a multifunctional reactor, and stir at 90-100° C. and 1000-1200 r / min for 120-240 minutes to make the mixture react uniformly to obtain a modified nylon mixed solution; S5 washing and drying: washing and precipitating the modified nylon mixed solution in step S4, and drying the precipitated modified nylon in a vacuum drying oven at a temperature of 60 to 80° C. for 2 to 3 days to obtain dried modified nylon particles; S6 Hybrid Processing: a. Stirring the modified nylon particles in step S5, 2 to 5 parts of nano-silicon dioxide and 0.5 to 2 parts of graphyne in a multifunctional reactor at a rate of 1000 to 1200 r / min for 120 to 240 minutes to uniformly mix them to obtain a mixed material; b. Melt-blending the mixed material through a twin-screw extruder, setting the extruder feeding zone temperature to 80-90° C., the melting zone temperature to 200-240° C., the die zone temperature to 220-250° C., and the rotation speed to 30-60 rpm, to extrude UV-resistant nylon fibers with a diameter of 1-5 mm; S7 Textile: Wind the fibers into yarn reels, use textile machines to weave the yarn into fabrics, dye, finish and enhance the fabrics to improve their wear resistance and obtain UV-resistant workwear fabrics.
[0008] In some of the embodiments, the nylon matrix may be a combination of one or more of nylon PA6 and nylon PA66.
[0009] In some embodiments, the acid treatment agent may be a combination of one or more of concentrated sulfuric acid, concentrated hydrochloric acid and phosphoric acid.
[0010] In some of the embodiments, when the lignocellulose nanofibers are pretreated in step S1 and modified by amino in step S4, the working environment needs to be ventilated 8 to 12 times per hour.
[0011] In some embodiments, when washing and precipitating the modified nylon mixed solution in step S5, 80 to 100 parts of deionized water are used for each washing, and the washing is repeated 3 to 5 times.
[0012] In some embodiments, in step S6, the UV-resistant nylon fiber needs to be cooled in a water bath with deionized water at 2 to 5° C. for 10 to 20 minutes to obtain a completely cured UV-resistant nylon fiber.
[0013] In some of the embodiments, the cured UV-resistant nylon fiber needs to be cleaned in deionized water at 50-60° C. and 0.1-0.3 parts of a cleaning agent to remove grease and impurities.
[0014] In some of the embodiments, the washed anti-ultraviolet nylon fiber needs to be dried in a low-temperature dryer to reduce the moisture content to 0.2% to 2%.
[0015] This reaction has the following advantages: (1) Anti-ultraviolet rays: By acid-amidating the nylon matrix and adding graphyne and nano-silica as ultraviolet absorbers, the prepared fabric can effectively block the penetration of ultraviolet rays; (2) Wear resistance: Graphene can be used as a reinforcing material to improve the wear resistance of fabrics, increase the tear resistance and abrasion resistance of fabrics, and extend the service life of fabrics; (3) Biodegradability: The lignin fiber nanofiber in the raw material is a renewable resource. Combined with the composite technology of nylon, the fabric has biodegradability while maintaining excellent performance, reducing the burden on the environment. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 : Microstructure of modified nylon fiber prepared in Example 7; Figure 2 : The microstructure of the modified nylon fiber prepared in Example 8; Figure 3 : The microstructure of the modified nylon fiber prepared in Comparative Example 1.
[0017] Figure 4 : The microstructure of the modified nylon fiber prepared in Comparative Example 2. DETAILED DESCRIPTION
[0018] The following will combine the technical process steps, specific implementation conditions and materials in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Example
[0019] Add 6 parts of lignin cellulose nanofibers and 80 parts of concentrated sulfuric acid to the multifunctional reactor, stir at a rate of 1300 r / min, and mix and stir at 15°C for 180 minutes. Continue to add 300 parts of deionized water to the multifunctional reactor, stir at a rate of 1000 r / min, mix and stir at 10°C for 20 minutes, and ultrasonically treat for 30 minutes to obtain a uniform suspension of lignin cellulose nanofibers for standby use. Example
[0020] Add 10 parts of lignin cellulose nanofibers and 100 parts of concentrated hydrochloric acid to the multifunctional reactor, stir at a rate of 1500 r / min, and mix and stir at 30°C for 240 minutes. Continue to add 200 parts of deionized water to the multifunctional reactor, stir at a rate of 1200 r / min, mix and stir at 30°C for 30 minutes, and ultrasonically treat for 60 minutes to obtain a uniform suspension of lignin cellulose nanofibers for use. Example
[0021] 85 parts of nylon PA6 and 180 parts of dimethylsulfamide were added to the multifunctional reactor in sequence, and stirred at a rate of 1000 r / min for 140 minutes to completely dissolve them to obtain a nylon solution for standby use. Example
[0022] 95 parts of nylon PA66 and 190 parts of dimethylsulfamide were added to the multifunctional reactor in sequence, and stirred at a rate of 1200 r / min for 180 minutes to completely dissolve them to obtain a nylon solution for standby use. Example
[0023] The lignocellulose nanofiber suspension in Example 1 and the dissolved nylon in Example 3 were added to a multifunctional reactor and stirred at a rate of 1200 r / min for 240 minutes. 60 parts of ammonia water, 1 part of p-toluenesulfonic acid, and 0.4 parts of hydroxytoluene were added to the multifunctional reactor, and stirred at a rate of 1200 r / min for 180 minutes at 100°C, and ventilated 8 times per hour during the period to make it react evenly to obtain a modified nylon mixed solution. The modified nylon mixed solution was washed and precipitated, and 100 parts of deionized water were used for each washing, and the washing was repeated three times. The precipitated modified nylon was dried in a vacuum drying oven at a temperature of 80°C and a drying time of 3 days to obtain dried modified nylon particles. Example
[0024] The lignocellulose nanofiber suspension in Example 2 and the dissolved nylon in Example 4 were added to a multifunctional reactor and stirred at a rate of 1000 r / min for 180 minutes. 50 parts of ammonia water, 0.5 parts of p-toluenesulfonic acid, and 0.3 parts of hydroxytoluene were added to the multifunctional reactor, and stirred at a rate of 1000 r / min for 120 minutes at 90°C, and ventilated 12 times per hour during the period to make it react evenly to obtain a modified nylon mixed solution. The modified nylon mixed solution was washed and precipitated, and 80 parts of deionized water were used for each washing, and the washing was repeated three times. The precipitated modified nylon was dried in a vacuum drying oven at a temperature of 60°C and a drying time of 2 days to obtain dried modified nylon particles. Example
[0025] The modified nylon particles in Example 5 were stirred with 3 parts of nano-silicon dioxide and 1 part of Graphene in a multifunctional reactor at a rate of 1200 r / min for 240 minutes to uniformly mix and obtain a mixture. The mixture was melt-blended by a twin-screw extruder, and the temperature of the extruder feeding zone was set to 90°C, the temperature of the melting zone was set to 220°C, the temperature of the die zone was set to 230°C, and the speed was set to 50 rpm to extrude an anti-ultraviolet nylon fiber with a diameter of 3 mm. The anti-ultraviolet nylon fiber was cooled in a water bath at 4°C for 10 minutes, the fiber was washed in warm water at 60°C and 0.3 parts of a detergent, and the fiber was dried in a low-temperature dryer to a moisture content of 0.8%. The fiber was wound into a yarn reel, and the yarn was woven into a fabric using a textile machine, and dyed, finished and enhanced to improve the wear resistance of the fabric to obtain an anti-ultraviolet workwear fabric.
[0026] The microstructure of the modified nylon fiber prepared by scanning electron microscopy is shown in Figure 1 a, the diameter of the nylon fiber is about 19.27 μm; the microstructure of the modified nylon fiber characterized by scanning electron microscopy is shown in Figure 1 b, it can be found that many active sites are well adhered to the surface of modified nylon fibers.
[0027] According to GB / T 18830 Evaluation of UV protection of textiles, the UV protection of workwear fabrics was measured. In the test, the UPF of the sample was 57, and T(UVA) AV =2.4%, it meets the national standard.
[0028] The wear resistance of workwear fabrics was measured according to GB / T 18830 Textiles - Determination of the abrasion resistance of fabrics by the Martindale method. In the test, the sample did not pill after 40,000 frictions, and was judged to have good wear resistance according to national standards. Example
[0029] The modified nylon particles in Example 6 were stirred with 4 parts of nano-silicon dioxide and 1.5 parts of graphyne in a multifunctional reactor at a rate of 1100 r / min for 180 minutes to uniformly mix and obtain a mixture. The mixture was melt-blended by a twin-screw extruder, and the temperature of the extruder feeding zone was set to 80°C, the temperature of the melting zone was set to 200°C, the temperature of the die zone was set to 220°C, and the speed was set to 40 rpm to extrude an anti-ultraviolet nylon fiber with a diameter of 4 mm. The anti-ultraviolet nylon fiber was cooled in a water bath at 3°C for 15 minutes, the fiber was washed in warm water at 50°C and 0.1 parts of a detergent, and the fiber was dried in a low-temperature dryer to a moisture content of 1.2%. The fiber was wound into a yarn reel, and the yarn was woven into a fabric using a textile machine, and dyed, finished and enhanced to improve the wear resistance of the fabric to obtain an anti-ultraviolet workwear fabric.
[0030] The microstructure of the modified nylon fiber prepared by scanning electron microscopy is shown in Figure 2 a, the diameter of the nylon fiber is about 15.38 μm; the microstructure of the modified nylon fiber characterized by scanning electron microscopy is shown in Figure 1 b, it can be found that many active sites are well adhered to the surface of modified nylon fibers.
[0031] According to GB / T 18830 Evaluation of UV protection of textiles, the UV protection of workwear fabrics was measured. In the test, the UPF of the sample was 51, and T(UVA) AV =2.8%, it meets the national standard.
[0032] The wear resistance of workwear fabrics was measured according to GB / T 18830 Textiles - Determination of the abrasion resistance of fabrics by the Martindale method. In the test, the sample did not pill after 40,000 frictions, and was judged to have good wear resistance according to national standards.
[0033] Comparative Example 1 Without adding nano-silicon dioxide and graphyne, the other steps are the same as in Example 7. The microstructure of the modified nylon fiber prepared by scanning electron microscopy is shown in Figure 4 , the diameter of the nylon fiber is about 28.77 μm; there are no active sites adhering to the surface of the modified nylon fiber.
[0034] According to GB / T 18830 Evaluation of UV protection of textiles, the UV protection of workwear fabrics was measured. In the test, the UPF of the sample was 35, and T(UVA) AV =6.2%, which does not meet the national standard.
[0035] The wear resistance of workwear fabrics was measured according to GB / T 18830 Textiles - Determination of the abrasion resistance of fabrics by the Martindale method. In the test, the sample was subjected to 18,000 friction pilling cycles, and according to national standards, it was judged that it did not have good wear resistance.
[0036] Comparative Example 2 The lignin fiber nanofibers were replaced with lignin fibers, and the other steps were the same as in Example 7. The microstructure of the modified nylon fiber prepared by scanning electron microscopy is shown in Figure 3 , the diameter of the nylon fiber is about 42.19 μm; there are no active sites adhering to the surface of the modified nylon fiber.
[0037] According to GB / T 18830 Evaluation of UV protection of textiles, the UV protection of workwear fabrics is measured. In the test, the UPF of the sample is 40, and T(UVA) AV =4.3%, it meets the national standard.
[0038] The wear resistance of workwear fabrics was measured according to GB / T 18830 Textiles - Determination of the abrasion resistance of fabrics by the Martindale method. In the test, the sample did not pill after 2000 frictions, and according to the national standard, it was judged that it did not have good wear resistance.
[0039] Technical personnel should note that: Although the present invention has been described according to the above specific implementation methods, the inventive concept of the present invention is not limited to this invention, and any modification using the inventive concept will be included in the scope of protection of this patent.
Claims
1. An anti-ultraviolet workwear fabric and a preparation method thereof, characterized in that: The raw material composition for manufacturing the anti-ultraviolet workwear fabric is as follows: 80-100 parts of nylon matrix, 5-10 parts of lignin cellulose nanofibers, 5-10 parts of ammonia, 80-100 parts of acid treatment agent, 40-60 parts of ammonia water, 180-200 parts of dimethylsulfamide, 0.5-1 part of p-toluenesulfonic acid, 500-700 parts of deionized water, 0.1-0.5 parts of hydroxytoluene, 2-5 parts of nano-silicon dioxide, and 0.5-2 parts of graphene; the specific steps of the preparation method of the anti-ultraviolet workwear fabric are as follows: S1 Pretreatment of wood cellulose nanofibers: Add 5-10 parts of lignin cellulose nanofibers and 80-100 parts of acid treatment agent into a multifunctional reactor, stir at a rate of 1300-1500 r / min, and mix and stir at 10-30°C for 180-240 minutes; S2 dispersion of wood cellulose nanofibers: continue to add 200-300 parts of deionized water to the multifunctional reactor in step S1, with a stirring rate of 1000-1200 r / min, mix and stir at 10-30°C for 20-30 minutes, and ultrasonically treat for 30-60 minutes to obtain a uniform wood cellulose nanofiber suspension; S3 dissolving nylon: add 80-100 parts of nylon matrix and 180-200 parts of dimethylsulfamide to the multifunctional reactor in sequence, and stir at a rate of 1000-1200 r / min for 120-240 minutes to completely dissolve the nylon matrix; S4 amino modification: a. Add the lignocellulose nanofiber suspension in step S2 and the dissolved nylon in step S3 into a multifunctional reactor, and stir at a rate of 1000 to 1200 r / min for 120 to 240 minutes; b. Add 40-60 parts of ammonia water, 0.5-1 parts of p-toluenesulfonic acid, and 0.1-0.5 parts of hydroxytoluene to a multifunctional reactor, and stir at 90-100° C. and 1000-1200 r / min for 120-240 minutes to make the mixture react uniformly to obtain a modified nylon mixed solution; S5 washing and drying: washing and precipitating the modified nylon mixed solution in step S4, and drying the precipitated modified nylon in a vacuum drying oven at a temperature of 60 to 80° C. for 2 to 3 days to obtain dried modified nylon particles; S6 Hybrid Processing: a. Stirring the modified nylon particles in step S5, 2 to 5 parts of nano-silicon dioxide and 0.5 to 2 parts of graphyne in a multifunctional reactor at a rate of 1000 to 1200 r / min for 120 to 240 minutes to uniformly mix them to obtain a mixed material; b. Melt-blending the mixed material through a twin-screw extruder, setting the extruder feeding zone temperature to 80-90° C., the melting zone temperature to 200-240° C., the die zone temperature to 220-250° C., and the rotation speed to 30-60 rpm, to extrude UV-resistant nylon fibers with a diameter of 1-5 mm; S7 Textile: Wind the fibers into yarn reels, use textile machines to weave the yarn into fabrics, dye, finish and enhance the fabrics to improve their wear resistance and obtain UV-resistant workwear fabrics.
2. The anti-ultraviolet workwear fabric and the preparation method thereof according to claim 1, characterized in that: The nylon matrix can be a combination of one or more of nylon PA6 and nylon PA66.
3. The anti-ultraviolet workwear fabric and the preparation method thereof according to claim 1, characterized in that: The acid treatment agent may be a combination of one or more of concentrated sulfuric acid, concentrated hydrochloric acid and phosphoric acid.
4. The anti-ultraviolet workwear fabric and the preparation method thereof according to claim 1, characterized in that: When the lignocellulose nanofibers are pretreated in step S1 and modified by amino in step S4, the working environment needs to be ventilated 8 to 12 times per hour.
5. The anti-ultraviolet workwear fabric and the preparation method thereof according to claim 1, characterized in that: When washing and precipitating the modified nylon mixed solution in step S5, 80 to 100 parts of deionized water are used for each washing, and the washing is repeated 3 to 5 times.
6. The anti-ultraviolet workwear fabric and the preparation method thereof according to claim 1, characterized in that: In the step S6, the anti-ultraviolet nylon fiber needs to be cooled in a water bath with deionized water at 2 to 5° C. for 10 to 20 minutes to obtain a completely cured anti-ultraviolet nylon fiber.
7. The anti-ultraviolet workwear fabric and the preparation method thereof according to claim 6, characterized in that: The cured UV-resistant nylon fiber needs to be cleaned in deionized water at 50-60°C and 0.1-0.3 parts of detergent to remove grease and impurities.
8. The anti-ultraviolet workwear fabric and the preparation method thereof according to claim 7, characterized in that: The anti-ultraviolet nylon fiber needs to be dried in a low-temperature dryer to reduce the moisture content to 0.2% to 2%.